2003
DOI: 10.1128/aem.69.5.2505-2511.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cell Culture-Taqman PCR Assay for Evaluation of Cryptosporidium parvum Disinfection

Abstract: Cryptosporidium parvum represents a challenge to the water industry and a threat to public health. In this study, we developed a cell culture-quantitative PCR assay to evaluate the inactivation of C. parvum with disinfectants. The assay was validated by using a range of disinfectants in common use in the water industry, including low-pressure UV light (LP-UV), ozone, mixed oxidants (MIOX), and chlorine. The assay was demonstrated to be reliable and sensitive, with a lower detection limit of a single infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
83
2
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 41 publications
1
83
2
7
Order By: Relevance
“…However, it is important to point out that during Ascaris egg development to the third-stage larva, the Ascaris egg grows from one cell to about 600 cells (35), which is significantly different from what happens in the life cycle of the single-celled prokaryotic protozoans Giardia and Cryptosporidium. For protozoans exposed to UV, infectivity studies or cell cultures are necessary to measure viability, because the DNA is not fully replicated until the organisms reproduce, after infection (16,18,33,38). In Ascaris, however, the complete DNA of the organism is replicated when the single cell in the egg undergoes the first two cell divisions before it differentiates into the germ and somatic cell lines that form the larva (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to point out that during Ascaris egg development to the third-stage larva, the Ascaris egg grows from one cell to about 600 cells (35), which is significantly different from what happens in the life cycle of the single-celled prokaryotic protozoans Giardia and Cryptosporidium. For protozoans exposed to UV, infectivity studies or cell cultures are necessary to measure viability, because the DNA is not fully replicated until the organisms reproduce, after infection (16,18,33,38). In Ascaris, however, the complete DNA of the organism is replicated when the single cell in the egg undergoes the first two cell divisions before it differentiates into the germ and somatic cell lines that form the larva (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the study of Cryptosporidium biology, cell culture methods have been used to study Cryptosporidium inactivation by disinfectants (4,13,23,26,28), efficacy of chemotherapeutic agents (3,5,34,37), and detection of infectious oocysts in water samples (1,7,10,17). The developmental stages of the parasite in cell culture are detected using a variety of techniques, including immunofluorescent assay microscopy (27), flow cytometry (31), reverse transcription-PCR (22), and quantitative PCR (5,8,11,15).…”
mentioning
confidence: 99%
“…Many C. parvum cell culture studies have used 48 h postinoculation as the endpoint of infection (16,24,26,28,29,31). In this study, CC-QSD revealed that infection at 48 h postinoculation was only 60% of the amount of infection at 72 h postinoculation.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, the CC-QSD standard curve generated by linear regression of mean background-subtracted CC-QSD C T values plotted against the log number of AHBSS-trypsin-treated oocysts inoculated per cell monolayer was sufficient. A similar relative quantitation approach using a DNA standard curve generated with only oocyst DNA, instead of infected cell monolayers, was recently reported for a disinfection study (16). The development of a universal standard curve for the absolute quantitation of infective C. parvum oocysts is a significant challenge.…”
Section: Discussionmentioning
confidence: 99%